17. THE CORRELATION BETWEEN SMILE CHARACTERISTICS AND ANGLE’S CLASSIFICATION OF FIRST-YEAR STUDENTS, UNIVERSITY OF MEDICINE AND PHARMACY, HANOI NATIONAL UNIVERSITY (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the relationship between smile characteristics and occlusion types according to Angle classification in first-year students at the University of Medicine and Pharmacy, Vietnam National University, Hanoi in 2022.Method: A cross-sectional study design on 96 students, aged 18-20. Data were collected through clinical examination, photography, observation of research subjects and analysis on SPSS software.Results: The height of the upper lip curve in the class II occlusion group was larger than that of the class I and class III occlusion groups. Smile height and mouth width had similar results between occlusion types; the class II canine occlusion had the highest rate of high smile lines; the class III canine occlusion group had the highest rate of low smile lines.Conclusion: There is a relationship between smile characteristics and types of occlusions according to Angle classification in first-year students; a larger sample size study is needed.
Keywords: Relationship; smile type; Angle occlusion; students